Safety Risk Analysis of LCT Type RoRo Vessel Berthing Process Using FMEA and Fuzzy FMEA Methods - Koyyimah, Putri Dinul; Putri, Destyariani Liana; Sudarni, Adiek Astika Clara (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2026)
The berthing process of Roll-on/Roll-off (RoRo) vessels of the Landing Craft Tank (LCT) type at Company X presents significant operational risks. This study analyzes safety risks using the Failure Mode and Effects Analysis (FMEA) and fuzzy FMEA methods. The highest RPN values from FMEA were found in ramp door placement (RPN = 50), safety cone installation (RPN = 48), and vehicle access (RPN = 45). Fuzzy FMEA identified ramp door risk (D20) as the top priority with FPRN = 134. Risk controls were proposed using the hierarchy of controls. Data were gathered from observations, interviews, and questionnaires with nine respondents. The integrated approach provided a more objective and practical risk analysis.